2015
DOI: 10.1089/bfm.2014.0078
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors Influencing the Decision to Breastfeed Newborns Conceived with IVF

Abstract: Long duration of infertility and history of cesarean delivery after IVF negatively influenced the breastfeeding initiation rate. For this subgroup of patients, postpartum care should be enhanced to support the early mother-baby relationship and promote breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
10
0
3
Order By: Relevance
“…We found that infants conceived via IVF were less likely to be DBF than infants conceived spontaneously. This finding is partially concordant with data in other cohorts who do not necessarily comprise of infants born very preterm, showing that mothers who conceived via IVF were less likely to exclusively DBF their infants yet were as likely to provide some DBF (Castelli et al, 2015;Fisher et al, 2013), if not more so (Hammarberg, Fisher, Wynter, & Rowe, 2011), than mothers who conceived spontaneously.…”
Section: Discussionsupporting
confidence: 87%
“…We found that infants conceived via IVF were less likely to be DBF than infants conceived spontaneously. This finding is partially concordant with data in other cohorts who do not necessarily comprise of infants born very preterm, showing that mothers who conceived via IVF were less likely to exclusively DBF their infants yet were as likely to provide some DBF (Castelli et al, 2015;Fisher et al, 2013), if not more so (Hammarberg, Fisher, Wynter, & Rowe, 2011), than mothers who conceived spontaneously.…”
Section: Discussionsupporting
confidence: 87%
“…Emzirmeye başlama oranları dünya genelinde oldukça farklıdır; bu oran Norveç, Danimarka ve Japonya'da yaklaşık %99, Almanya'da %90 ve ABD'de %74,6'dır [10]. Türkiye Nüfus Sağlığı Araştırması (TNSA) 2013 verilerine göre Türkiye'de bu oranın sağlık çalışanlarının yardımıyla %70'lerde olduğu bildirilmektedir [11].…”
Section: Discussionunclassified
“…Monti ve ark. 'ı [10,26] YÜT ile gebe kalan kadınlarda daha fazla anksiyete ve emosyonel kırılganlık olduğunu, bunun depresyon riskini arttırdığını ve annebebek ilişkisi üzerine olası olumsuz sonuçlarını vurgulamaktadırlar. Castelli ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Previous studies on breastfeeding showed that preterm infants, low birthweight infants, males and infants with health issues following delivery have a decreased probability of being breastfed, as well as a shorter mean breastfeeding duration 4 . Maternal factors associated with breastfeeding outcomes included maternal age, smoking, obesity and low level of maternal education 2,4,5 . Furthermore, caesarean section was reported to be associated with lower breastfeeding initiation rate and shorter mean breastfeeding duration 2,4,5 …”
Section: Introductionmentioning
confidence: 99%